Increasing medication assisted treatment in rural primary care practice: a qualitative comparative analysis from IT MATTTRs Colorado - Holtrop, Jodi Summers; Mullen, Rebecca; Curcija, Kristen; Rubinson, Claude; Westfall, John M.; Nease, Donald E.; Zittleman, Linda (Frontiers in Medicine, 2024)
Purpose: Opioid dependence and use disorders (OUDs) are serious public health crises resulting in a rising number of opioid-related deaths. Medication assisted treatment (MAT), in this case treatment with buprenorphine, is an evidence-based solution to combatting OUD; however, MAT has been largely unavailable in rural areas. This study investigated what it took to increase MAT in rural Colorado primary care practices. Methods: Mixed methods study using qualitative and quantitative data collected from interviews, observations, surveys, and practice-reported data. Participants were staff members from 35 rural primary care practices in Colorado, USA. We qualitatively analyzed the data, then transformed the data, then analyzed it using qualitative comparative analysis (QCA). Results: Having a MAT waivered prescribing clinician on staff and a MAT system in place were necessary conditions to providing MAT (consistency = 1.0; coverage = 0.53 & 0.39 respectively). Practice size (number of providers) was associated with differences in conditions that provided sufficient aspects for MAT provision. Small (1-2 medical providers), non-private practices benefited from the presence of behavioral health and a clinician with MAT experience. Medium sized practices (3-5 providers) whether private or not benefited from behavioral health, often in combination with a clinician with MAT experience. In large practices (6 or more providers), behavioral health was not a factor while having a clinician with MAT experience mattered half of the time. Conclusions: Implementation of MAT in rural primary care is a complex task that may benefit from the resources of behavioral health and a clinician with prior MAT experience.